Correlation of renal cortical blood perfusion and BP response after renal artery stenting - Wang, Siyu; Zhang, Sijie; Li, Yan; Ma, Na; Li, Mengpu; Ai, Hu; Zhu, Hui; Ren, Junhong; Li, Yongjun; Li, Peng (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to observe the correlation between renal cortical blood perfusion (CBP) parameters and BP response in patients with severe renal artery stenosis (RAS) who underwent stenting. Methods This was a single-center retrospective cohort study. A total of 164 patients with unilateral severe RAS after successful percutaneous transluminal renal artery stenting in Beijing Hospital from October 2017 to December 2020 were included. According to the results of BP evaluated at 12 months, all patients were divided into the BP response group (n = 98) and BP nonresponse group (n = 66). The baseline clinical and imaging characteristics and follow-up data about 24 h ABPM and CBP were recorded and analyzed. Pearson correlation analysis was used to evaluate the relationship between CBP parameters and 24 h average SBP. Univariate and multivariate logistic regression analysis was used to evaluate the risk factors for BP response. Results Among 164 patients with severe RAS, there were 100 males (61.0%), aged 37–75 years, with an average of 56.8 ± 18.4 years, and average artery stenosis of 84.0 ± 12.5%. The BP nonresponse patients had a longer duration of hypertension, more current smoking subjects and diabetic patients, lower eGFR, increased number of hypertensive agents, and rate of insulin compared with the BP response group (P < 0.05). After PTRAS, patients in the BP response group were associated with significantly lower BP and improved CPB, characterized by increased levels of maximum intensity (IMAX), area under ascending curve (AUC1), area under the descending curve (AUC2), shortened rising time (RT), mean transit time (mTT), and prolonged time to peak intensity (TTP; P < 0.05). However, the BP nonresponse group was only associated with significantly reduced RT (P < 0.05) compared with baseline data. During an average follow-up of 11.5 ± 1.7 months, the BP response group was associated with significantly lower levels of SBP, DBP, 24 h average SBP, and 24 h average DBP compared with the nonresponse group (P < 0.05). Pearson correlation analysis showed that the the pre-operative CBP parameters, including IMAX (r = 0.317), RT (r = 0.249), AUC1 (r = 0.614), AUC2 (r = 0.558), and postoperative CBP parameters, including RT (r = 0.283), AUC1 (r = 0.659), and AUC2 (r = 0.674) were significantly positively correlated with the 24 h average SBP, while the postoperative TTP (r = −0.413) and mTT (r = −0.472) were negatively correlated with 24 h average SBP (P < 0.05). Multivariate Logistic regression analysis found that diabetes (OR = 1.294), NT-proBNP (OR = 1.395), number of antihypertensive agents (OR = 2.135), pre-operation IMAX (OR = 1.534), post-operation AUC2 (OR = 2.417), and baseline dDBP (OR = 2.038) were related factors for BP response (all P < 0.05). Conclusion Patients in the BP nonresponse group often have diabetes, a longer duration of hypertension, significantly reduced glomerular filtration rate, and heavier renal artery stenosis. CBP parameters are closely related to 24 h average SBP, and pre-operation IMAX and post-operation AUC2 are markers for a positive BP response.